Songbird trend estimation and density-habitat relationships to inform and prioritize conifer management in the sagebrush and pinyon-juniper ecotone - Van Lanen, Nicholas J., author; Aldridge, Cameron L., advisor; Pejchar, Liba, committee member; Koons, David N., committee member; Bailey, Larissa L., committee member (Colorado State University. Libraries, 2022)
To view the abstract, please see the full text of the document.
Keywords: multi-species management; pinyon jay; sagebrush; non-target species; conifer removal; pinyon-juniper